Simultaneous measurement of CO 2 sorption and swelling of phosphate-based ionic liquid - Wang,J; Petit,C; Zhang,X; Park,AHA (Green Energy and Environment, 2016)
The development of alternative CO 2 capture solvents such as ionic liquids (ILs) and nanoparticle organic hybrid materials (NOHMs) have provided interesting options for CO 2 capture. In this study, CO 2 interactions with 1,3-dimethylimidazolium dimethylphosphate ([MMIM]DMP), 1-ethyl-3-methylimidazolium dimethylphosphate ([EMIM]DMP) and 1-ethyl-3-methylimidazolium diethylphosphate ([EMIM]DEP) that contain inorganic ester groups based on phosphate, were investigated using ATR FT-IR spectroscopy. CO 2 -induced swelling, CO 2 diffusivity and CO 2 capture capacity were simultaneously measured to identify CO 2 capture mechanisms, kinetics and diffusion behaviors as a function of the alkyl chain length of the cation. Henry's law constants of CO 2 were found to be in the range of 4–11 MPa, which is in agreement with those reported in other studies.